(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The Indian companies are provided with a global reporting landscape with the introduction of Indian Accounting Standards (Ind AS). These standards are in line with the global International Financial Reporting Standards (IFRS) and have made the financial statements comparable at a global level. In India, the MCA gave a strategic plan for the introduction of Ind AS, which are in line with IFRS, in 2010. A planned roadmap was given for the adoption of Ind AS voluntarily from April 2015, mandatorily for all companies with a net worth of 500 crore or more from April 2016, and so on in a phased manner. The objective of the research is to analyze the impact of Ind AS adoption on the financial performance of selected companies in India, based on the cutoff year 2016. Data from 39 eligible companies (ranging from 2012-2023) was collected, and hypotheses were tested using paired sample t-tests. The results show that there is no significant impact of Ind AS adoption on the financial ratios of the selected companies. The study has practical implications for the companies that are still lagging behind in reporting Ind AS data and companies for whom adoption is still voluntary, as findings suggest that adoption and reporting of Ind AS do not affect the financial performance of the company.